1991
DOI: 10.1007/bf01250373
|View full text |Cite
|
Sign up to set email alerts
|

Brain kinetics of L-[?-11 C]DOPA in humans studied by positron emission tomography

Abstract: The in vivo dopamine precursor L-3,4-dihydroxyphenylalanine (L-DOPA) labelled with 11C in the beta position has been used for positron emission tomography studies of L-DOPA utilization in the brain. The brain uptake and kinetics of L-[11C]DOPA-derived radioactivity were studied in healthy male volunteers, and the specific utilization, i.e. decarboxylation rate of L-[11C]DOPA in different brain areas, was quantified using a brain region devoid of specific L-[11C]DOPA utilization as reference. Total uptake of L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 25 publications
0
53
1
Order By: Relevance
“…Tissue slope-intercept plots for FDOPA (Hartvig et al, 1991;Hoshi et al, 1993) were plotted for the four telencephalic ROIs. In the calculation of ordinate values, the radioactivity concentrations in CB were subtracted from those in each ROI to correct for the presence of non-specific background tissue radioactivity -i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue slope-intercept plots for FDOPA (Hartvig et al, 1991;Hoshi et al, 1993) were plotted for the four telencephalic ROIs. In the calculation of ordinate values, the radioactivity concentrations in CB were subtracted from those in each ROI to correct for the presence of non-specific background tissue radioactivity -i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al (1990a,b), who used FDOPA, found the plot to be linear between 30 and 90 min of real time. Hartvig et al (1991), who used L-[!3_ 11 C]DOPA, found the plot to be linear after 5 min of "integral time." In this study, we found the plot more linear between 30 and 90 min (the 30-90-min analysis) than between 5 and 90 min (the 5-90-min analysis) because the slope declined during the early phase of the study and reached an asymptote around 30 min (Fig.…”
Section: Md(t) + Mm(t) R(t) = M�(t) + M�(t)mentioning
confidence: 99%
“…4). Whatever it may be called, the slope of the reference tissue graphic analysis implicitly assumes that the fraction of FDOPA in the reference tissue remains constant over time (Hartvig and others 1991), whereas it is known that within 30 minutes after FDOPA injection, OMFD becomes the predominant Healthy subjects 0.0041 ± 0.0012 0.0037 ± 0.0015 Schizophrenia 0.0080 ± 0.0038 0.0063 ± 0.0029…”
Section: Gjedde-patlak Linear Graphic Analysis Applied To Fdopamentioning
confidence: 99%